How experience with tone in the native language affects the L2 acquisition of pitch accents - Zahner-Ritter, Katharina; Zhao, Tianyi; Einfeldt, Marieke; Braun, Bettina (Frontiers in Psychology, 2022)
This paper tested the ability of Mandarin learners of German, whose native language has lexical tone, to imitate pitch accent contrasts in German, an intonation language. In intonation languages, pitch accents do not convey lexical information; also, pitch accents are sparser than lexical tones as they only associate with prominent words in the utterance. We compared two kinds of pitch-accent contrasts: (1) a “non-merger” contrast, which Mandarin listeners perceive as different and (2) a “merger” contrast, which sounds more similar to Mandarin listeners. Speakers of a tone language are generally very sensitive to pitch. Hypothesis 1 (H1) therefore stated that learners produce the two kinds of contrasts similarly to native German speakers. However, the documented sensitivity to tonal contrasts, at the expense of processing phrase-level intonational contrasts, may generally hinder target-like production of intonational pitch accents in the L2 (Hypothesis 2, H2). Finally, cross-linguistic influence (CLI) predicts a difference in the realisation of these two contrasts as well as improvement with higher proficiency (Hypothesis 3, H3). We used a delayed imitation paradigm, which is well-suited for assessing L2-phonetics and -phonology because it does not necessitate access to intonational meaning. We investigated the imitation of three kinds of accents, which were associated with the sentence-final noun in short wh-questions (e.g., Wer malt denn Mandalas, lit: ‘Who draws PRT mandalas?’ ‘Who likes drawing mandalas?’). In Experiment 1, 28 native speakers of Mandarin participated (14 low- and 14 high-proficient). The learners’ productions of the two kinds of contrasts were analysed using General Additive Mixed Models to analyse differences in pitch-accent contrasts over time, in comparison to the productions of native German participants from an earlier study (Zahner-Ritter et al., 2022). Results showed a more pronounced realisation of the non-merger contrast compared to German natives and a less distinct realisation of the merger contrast, with beneficial effects of proficiency, lending support to H3. Experiment 2 tested low-proficient Italian learners of German (whose L1 is an intonation language) to contextualise the Mandarin data and further investigate CLI. Italian learners realised the non-merger contrast more target-like than Mandarin learners, lending additional support to CLI (H3).